A Plasma‐Assisted Route to the Rapid Preparation of Transition‐Metal Phosphides for Energy Conversion and Storage. Issue 7 (6th June 2017) - Liang, Hanfeng; Alshareef, Husam N.
Abstract : Transition‐metal phosphides (TMPs) are important materials that have been widely used in catalysis, supercapacitors, batteries, sensors, light‐emitting diodes, and magnets. The physical and chemical structure of a metal phosphide varies with the method of preparation as the electronic, catalytic, and magnetic properties of the metal phosphides strongly depend on their synthesis routes. Commonly practiced processes such as solid‐state synthesis and ball milling have proven to be reliable routes to prepare TMPs but they generally require high temperature and long reaction time. Here, a recently developed plasma‐assisted conversion route for the preparation of TMPs is reviewed, along with their applications in energy conversion and storage, including water oxidation electrocatalysis, sodium‐ion batteries, and supercapacitors. The plasma‐assisted synthetic route should open up a new avenue to prepare TMPs with tailored structure and morphology for various applications. In fact, the process may be further extended to the synthesis of a wide range of transition‐metal compounds such as borides and fluorides at low temperature and in a rapid manner. Abstract : Transition‐metal phosphides (TMPs) are important materials for various applications. The recent progress in plasma‐assisted rapid synthesis of TMPs is introduced. In addition, their applications in energy conversion and storage, including electrocatalysis, sodium‐ion batteries, and supercapacitors are also summarized.